Predictive control for the operation of cascade pumping stations in water supply canal systems considering energy consumption and costs. (1st July 2023) - Kong, Lingzhong; Li, Yueqiang; Tang, Hongwu; Yuan, Saiyu; Yang, Qian; Ji, Qingfeng; Li, Zhipeng; Chen, Ruibin
Highlights: A closed-loop control method for the operation of water-supply canal systems (WSCSs) with pumps was proposed. The proposed method could reduce the operating energy and cost by 5.1 % and 5.5 %, respectively, under energy- and cost-driven. Compared with the open-loop method, the proposed method can maintain satisfactory results under uncertain disturbance. It is difficult to significantly reduce operating costs through load shifting when pumps in WSCSs are operating efficiently. Abstract: Water supply canal systems (WSCSs) have a significant environmental and energetic impact due to the large amount of energy consumed in water pumping and water losses. The safe and efficient operation of these systems is crucial. This study presents a closed-loop predictive control method for the operation of pumping stations in WSCSs, considering operation safety and energy consumption. In the proposed method, a linear prediction model derived from the hydrodynamic model is used for state prediction; data assimilation is used to correct the prediction model based on the feedback water level information; on the basis of the prediction results, the optimization control model for energy or cost saving is rolling established and solved to obtain the optimal pump control strategy. The method was tested on a virtual simulation model of a WSCS with two pumping stations under uncertain disturbances and compared to an open-loop optimal control method. The results demonstrated that the proposed method's cost- and energy-driven optimization strategies could reduce the system's operating energy and cost by 5.1 % and 5.5 %, respectively while ensuring the safe operation of the system. Compared with the result of 1.4 % energy reduction and 0.2 % cost reduction under the open-loop optimal control, the proposed method can retain a better optimization effect under uncertain disturbance and has good robustness. Furthermore, the method can be modified according to the needs of the WSCSs for pump control.